(untitled) (Journal of Contemporary Educational Policies and Practices, 2021)
In the trend of Education 4.0, the assessment of learning results through online tests is increasingly widespread and important because of its usability and mobility. In addition, it is also adaptable in the volatile situations of today’s society such as natural disasters, epidemics, war, etc. The paper presents the results of an empirical study in Mathematics at high schools in Can Tho city on the comparison of outcomes between online tests and paper tests. The initial statistical analysis results show that the evaluation of learning results by online tests has high consensus among the experimental group. Furthermore, the advantages and suggestions for improvement are also pointed out and discussed in this work.